Development and validation of a HILIC-HPLC-ELSD method for simultaneous determination of glucosamine hydrochloride and chondroitin sulfate in dietary supplements - Etik Wahyuningsih; Riesta Primaharinastiti; Mochammad Yuwono (Universidade de São Paulo, 2023)
Abstract The objective of the present study is to develop and validate a simple, selective and accurate hydrophilic interaction liquid chromatography - a high performance liquid chromatography incorporating an evaporative light scattering detector (HILIC-HPLC-ELSD) method for simultaneously determining glucosamine hydrochloride and chondroitin sulfate in dietary supplements. The chromatographic separation was carried out on a ZIC-HILIC column (150 mm x 4.6 mm x 5µm) in isocratic system mode with a mobile phase of acetonitrile, 30 mM ammonium formate and water (77:20:3, v/v/v) at pH 4.5, a column temperature of 35°C, a flow rate of 1 mL.min-1, and an injection volume of 5 µL. An evaporative light scattering (ELS) detector was used. Effective separation was achieved by means of analyte resolution of more than 1.5 with an analysis run time of approximately 20 minutes. The linearity of glucosamine hydrochloride and chondroitin sulfate ranged from 0.4 to 2.5 mg.mL-1. The limits of the detection and quantification of glucosamine hydrochloride were 20 and 80 mg.mL-1 respectively, while for chondroitin sulfate they were 80 and 400 mg.mL-1. All validation parameters satisfied the acceptance criteria in accordance with International Conference on Harmonisation (ICH) guidelines. The method was successfully applied to the assay of commercial dietary supplement samples.